Scott LaFaro - Chevan, David (The Grove Dictionary of American Music, 2013)
"The Grove Dictionary of American Music" published on by Oxford University Press.
Keywords: Music; Regional and Area Studies; Social sciences; dept.mus

Red Nichols - Chevan, David (The Grove Dictionary of American Music, 2013)
"The Grove Dictionary of American Music" published on by Oxford University Press.
Keywords: Music; Regional and Area Studies; Social sciences; dept.mus

Ray(mond) Brown - Chevan, David (The Grove Dictionary of American Music, 2013)
"The Grove Dictionary of American Music" published on by Oxford University Press.
Keywords: Music; Regional and Area Studies; Social sciences; dept.mus

Kid Ory - Chevan, David (The Grove Dictionary of American Music, 2013)
"The Grove Dictionary of American Music" published on by Oxford University Press.
Keywords: Music; Regional and Area Studies; Social sciences; dept.mus

Jimmy Blanton - Chevan, David (The Grove Dictionary of American Music, 2013)
"The Grove Dictionary of American Music" published on by Oxford University Press.
Keywords: Music; Regional and Area Studies; Social sciences; dept.mus

Doc Cheatham - Chevan, David (The Grove Dictionary of American Music, 2013)
"The Grove Dictionary of American Music" published on by Oxford University Press.
Keywords: Music; Regional and Area Studies; Social sciences; dept.mus